Effectiveness of Safety management practice in construction projects - MOHAMMED ABOUD MAFAILEH, ALA (IRC, 2016)
There have been significant reductions in the number and the rate of injury in general over the last 20 years or more. However, construction industry remains as one of the risky industries. The purpose of this study is to examine the factors affecting safety management in the Malaysian construction industry, as well as to highlight the importance of safety management in construction industry. The industry has contributed significantly to the economic growth of the country. Nonetheless, when construction safety management is not implemented systematically, accidents will happen and this will affect the economic growth of the country. This study put the safety management in construction project as one of the most important elements for project performance and success. The main focus of this study is building construction industry in Malaysia. The research started with gathering information through literature review about factors that might affect the standards of safety in construction industry, as well as importance of safety management in construction industry. Then, a study questionnaire was prepared based on the literature review. Once the questionnaire prepared, pilot survey has been conducted to improve and refine the main questionnaire. After obtaining the main questionnaire result's, this data went through three analysis methods, which were the Relative Importance Index (RII), Average Index (AI), and Cronbach's alpha using SPSS software. Logistical, technical and other issues or problems have been addressed. In this study, it was found that improvements in many aspects need to be considered and monitored frequently in order to ensure the effectiveness of the safety management system in construction projects